Induction and coexpression of latent transforming growth factor β-binding protein-1 and fibrillin-1 in experimental glomerulonephritis - Porst, Markus; Daniel, Christoph; Plank, Christian; Schocklmann, Harald O.; Reinhardt, Dieter P.; Hartner, Andrea (Nephron Experimental Nephrology, 2006)
Background: Latent transforming growth factor-β-binding protein 1 (LTBP-1) and fibrillin-1 were shown to colocalize and interact in the extracellular matrix of the skin and vasculature. This interaction may regulate transforming growth factor-β (TGF-β) activity. TGF-β is an important progression factor for glomerular diseases. We hypothesized that LTBP-1 and fibrillin-1 are coexpressed in the glomerulus and upregulated during glomerulonephritis. Methods: Acute anti-Thy1.1 glomerulonephritis was induced with a single intravenous injection (1 mg/kg body weight) of a monoclonal anti-Thy1.1 antibody in rats. Real-time RT-PCR and immunohistochemical analyses for LTBP-1 and fibrillin-1 were performed. Results: Induction of glomerular LTBP-1 mRNA was detected on day 2 of disease, while mRNA for fibrillin-1 was already upregulated 1 day after induction of disease. Both LTBP-1 and fibrillin-1 showed a mesangial distribution. An expansion of the LTBP-1 and fibrillin-1-positive mesangial area was seen on day 6 of disease, when transient matrix accumulation was most prominent. On day 12 of disease, glomerular LTBP-1 and fibrillin-1 immunoreactivities had returned to control levels. In serial sections, some colocalization of LTBP-1 and fibrillin-1 was detected in control as well as in nephritic glomeruli. Conclusion: Mesangial expression of LTBP-1 and fibrillin-1 is induced early in experimental nephritis and LTBP-1 and fibrillin-1 are partially colocalized in the nephritic glomerulus. An interaction of these molecules could stabilize latent TGF-β complexes and thus attenuate the activation of TGF-β during this self-limited glomerular disease. Copyright © 2006 S. Karger AG.
Created from Fastlane, Scopus look-up
Keywords: Anti-Thy1.1 nephritis; Extracellular matrix; Glomerulus; Mesangial cells; Microfibrillar proteins; Transforming growth factor-β